YOUTH, DIGITAL CULTURE, AND SOCIAL CHANGE IN MODERN AZERBAIJAN - Kamran Ali Oglu Hasanov; Aygun Kazimova; Aysel Mammadova; Fatemeh Zahra Rahimi; Hossein Reza Farhadi (CV. Tirta Pustaka Press, 2026)
This study addresses the limited empirical research on how youth in Azerbaijan navigate digital culture under socio-political constraints, a post-Soviet society undergoing rapid digitalization and socio-political transformation. Using a qualitative design with purposive sampling, data were analyzed through thematic analysis to capture in-depth youth experiences. The findings show that Azerbaijani youth strategically use digital platforms to express dissent through indirect and culturally adaptive practices, allowing youth to navigate cultural norms, express alternative narratives, and engage in social activism. The study identifies state surveillance and regulatory restrictions as primary constraints shaping youth digital engagement, which limit the scope and impact of online participation. These dual dynamics underscore the ambivalent role of digital culture as both an enabler of empowerment and a site of constraint. The study contributes to a nuanced understanding of how Azerbaijani youth strategically employ digital media to negotiate social, cultural, and political realities, while also revealing the contingent nature of digital-driven social change in transitional societies. The study recommends context-specific policies to improve digital literacy and protect youth civic expression in regulated digital environments. The study also provides directions for future research, including comparative analyses across post-Soviet contexts and intersectional examinations of digital participation. Overall, this research illuminates the transformative potential and limitations of digital culture in shaping youth agency and social change in modern Azerbaijan.